Crashworthiness Analysis of Hierarchical Multi-Cell Circular Structures Made of Recycled Aa6061 Aluminium Alloys for Sustainable Automotive Crash Box - Muhammad Rafiuddin Ekhwan; SUBRAMANIAM, S KANNA; Susharrman (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The crashworthiness of automotive structures is crucial for vehicle safety, particularly in reducing impact forces during collisions. Hierarchical multi-cell (HMC) crash box designs, made from recycled AA6061 aluminium alloys, offer superior energy absorption and lightweight properties. However, many existing designs lack thorough evaluation under dynamic axial impact conditions, which may affect energy dissipation and structural integrity. This study analyzes stress distribution, deformation behavior, and key metrics such as Specific Energy Absorption (SEA) and Peak Crushing Force (PCF) in both traditional and HMC crash boxes under axial impact. The methodology includes 3D modeling using ANSYS Workbench and Finite Element Analysis (FEA) simulations. Results show that the conventional crash box design recorded a peak deformation of 0.031302 meters and a peak crushing force (PCF) of 4246 N, while the HMC design achieved a peak deformation of 0.022479 meters and a PCF of 3417.5 N. This indicates that the HMC design absorbed impact energy more efficiently, resulting in 6.7% less deformation and a lower peak crushing force. Additionally, the HMC crash box demonstrated a higher Specific Energy Absorption (SEA) of 6962.8 J/kg, compared to 5611.8 J/kg for the conventional crash box, further proving that the HMC design provides better energy dissipation and enhanced crashworthiness. This research introduces an innovative HMC crash box design from recycled AA6061 aluminium alloys, enhancing energy dissipation, material efficiency, and structural resilience for safer, sustainable automotive components.